Metropolitan Governance of Transport and Land Use in Chicago - Merk, Olaf (OECD Regional Development Working Papers, 2014)
This study aims to assess the degree of institutional fragmentation of transport and land use planning in Chicago and to assess the main challenges related to this institutional fragmentation. It provides an overview of local governments in metropolitan Chicago and mechanisms for metropolitan coordination, including organisations at the metropolitan scale, dealing with planning, land use and transport. Five main challenges related to institutional fragmentation in transport and land use planning are identified: a lack of (1) interconnectivity, (2) coherence across transit modes, (3) regional freight planning, (4) accountability and (5) implementation power of regional planning and transport objectives. These challenges are analysed. The concluding section suggests some avenues for reform that could be explored in order to overcome the challenges of metropolitan fragmentation in transport and land use in Chicago